The Effectiveness of Coffee Cherry Extract as a Neuroprotector in High-Fat Diet and Streptozotocin-Induced Diabetic Rats with Cognitive Impairment - Muhammad Zulfadhli (UMSU, 2026)
Background: Diabetes mellitus causes chronic hyperglycemia that induces oxidative stress, inflammation, and neuronal damage, leading to cognitive impairment. Coffee cherry contains bioactive compounds (polyphenols, flavonoids, caffeine, chlorogenic acid) with neuroprotective potential. Objective: To evaluate the effect of coffee cherry extract on cognitive function, brain-derived neurotrophic factor (BDNF), and oxidative stress in diabetic rats induced by high-fat diet (HFD) and streptozotocin (STZ). Methods: A post-test only control group design was applied using 36 male Wistar rats divided into six groups: normal control, negative control, HFD+STZ, HFD+STZ+metformin 200 mg/kgBW, HFD+STZ+coffee cherry extract 100 mg/kgBW, and HFD+STZ+coffee cherry extract 200 mg/kgBW. Parameters measured included blood glucose, spatial memory (Y-maze), brain BDNF (ELISA), and malondialdehyde (MDA). Data were analyzed using ANOVA and post hoc tests, with p0.05 considered significant. Results: Coffee cherry extract at 100 and 200 mg/kgBW significantly reduced blood glucose (p0.05), improved Y-maze alternation, increased BDNF, and decreased MDA compared to untreated HFD+STZ rats. The 200 mg/kgBW dose showed the strongest effect, comparable or superior to metformin in some parameters. Conclusion: Coffee cherry extract provides neuroprotection through oxidative stress reduction and BDNF enhancement, thereby improving cognitive function in diabetic rats.